2013
DOI: 10.1002/jrs.4279
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of styrene polymerization using Raman spectroscopy. Multi‐scale approach of homogeneous and heterogeneous polymerization processes

Abstract: International audienceFree radical polymerization of styrene was monitored in situ by combining Raman spectroscopy to other experimental techniques (gravimetry and rheology). Three different processes were investigated: bulk, emulsion and miniemulsion polymerization. A complete analysis of the evolution of Raman spectrum during the course of reaction showed that a lot of information about molecular dynamics could be extracted and related to chemical phenomena. In addition, we report for the first time the coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
(74 reference statements)
4
30
0
Order By: Relevance
“…Increasing surfactant concentration led to faster monomer consumption as was expected on the basis of classical theory of emulsion polymerization . In addition, in previous work, we showed that similar linear correlation existed in both emulsion and miniemulsion polymerization conditions . Even if the wavenumbers were slightly higher in miniemulsion conditions as compared with emulsion conditions, the slope of the linear variation with monomer conversion was almost the same for both processes.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Increasing surfactant concentration led to faster monomer consumption as was expected on the basis of classical theory of emulsion polymerization . In addition, in previous work, we showed that similar linear correlation existed in both emulsion and miniemulsion polymerization conditions . Even if the wavenumbers were slightly higher in miniemulsion conditions as compared with emulsion conditions, the slope of the linear variation with monomer conversion was almost the same for both processes.…”
Section: Resultssupporting
confidence: 82%
“…Indeed, a Raman shift of 2 cm −1 of the wavenumber ( ω 0 ) as well as an increase of the bandwidth (linked with σ 1/2 ) was detected over the course of the reaction. Same changes have already been noticed independently of the studied polymerization process, bulk, emulsion, or miniemulsion . These observations suggested that this analysis of Raman data could be applied to other processes.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations